Constructing Outcomes in Teacher Education - Cochran-Smith, Marilyn (Education Policy Analysis Archives, 2001)
As we enter the twenty-first century, the outcomes, consequences, and results of teacher education have become critical topics in nearly all of the state and national policy debates about teacher preparation and licensure as well as in the development of many of the privately and publicly funded research agendas related to teacher and student learning. In this article, I argue that teacher education reform over the last fifty years has been driven by a series of questions about policy and practice. The question that is currently driving reform and policy in teacher education is what I refer to as "the outcomes question." This question asks how we should conceptualize and define the outcomes of teacher education for teacher learning, professional practice, and student learning, as well as how, by whom, and for what purposes these outcomes should be documented, demonstrated, and/or measured. In this article, I suggest that the outcomes question in teacher education is being conceptualized and constructed in quite different ways depending on the policy, research, and practice contexts in which the question is posed as well as on the political and professional motives of the posers. The article begins with an overview of the policy context, including those reforms and initiatives that have most influenced how outcomes are currently being constructed, debated, and enacted in teacher education. Then I identify and analyze three major "takes" on the outcomes question in teacher educationoutcomes as the long-term or general impacts of teacher education, outcomes as teacher candidates' scores on high stakes teacher tests, and outcomes as the professional performances of teacher candidates, particularly their demonstrated ability to influence student learning. For each of these approaches to outcomes, I examine underlying assumptions about teaching and schooling, the evidence and criteria used for evaluation, units of analysis, and consequences for the profession. I point out that how we construct outcomes in teacher education (including how we make the case that some outcomes matter more than others) legitimizes but also undermines particular points of view about the purposes of schooling, the nature of teaching and learning, and the role of teacher education in educational reform. In the second half of the article, I offer critique across the three constructions of outcomes, exploring the possibilities as well as the pitfalls involved in the outcomes debate. In this section, I focus on the tensions between professional consensus and critique, problems with the inputs-outputs metaphor, the need to get social justice onto the outcomes agenda, problems with the characterization of teachers as either saviors or culprits, and the connection of outcomes to educational reform strategies that are either democratic or market-driven.